Efficient and equitable design of marine protected areas in Fiji through inclusion of stakeholder‐specific objectives in conservation planning. Issue 5 (27th April 2015) - Gurney, Georgina G.; Pressey, Robert L.; Ban, Natalie C.; Álvarez‐Romero, Jorge G.; Jupiter, Stacy; Adams, Vanessa M.
Abstract The efficacy of protected areas varies, partly because socioeconomic factors are not sufficiently considered in planning and management. Although integrating socioeconomic factors into systematic conservation planning is increasingly advocated, research is needed to progress from recognition of these factors to incorporating them effectively in spatial prioritization of protected areas. We evaluated 2 key aspects of incorporating socioeconomic factors into spatial prioritization: treatment of socioeconomic factors as costs or objectives and treatment of stakeholders as a single group or multiple groups. Using as a case study the design of a system of no‐take marine protected areas (MPAs) in Kubulau, Fiji, we assessed how these aspects affected the configuration of no‐take MPAs in terms of trade‐offs between biodiversity objectives, fisheries objectives, and equity in catch losses among fisher stakeholder groups. The achievement of fisheries objectives and equity tended to trade‐off concavely with increasing biodiversity objectives, indicating that it is possible to achieve low to mid‐range biodiversity objectives with relatively small losses to fisheries and equity. Importantly, the extent of trade‐offs depended on the method used to incorporate socioeconomic data and was least severe when objectives were set for each fisher stakeholder group explicitly. We found that using different methods to incorporate socioeconomic factors that require similar data and expertise can result in plans with very different impacts on local stakeholders.